An optoelectronic system for controlling a direct current motor. PART 1: ELECTRICAL AND ELECTRONIC DESIGN - Syroka, Zenon (Technical Sciences, 2022)
An optoelectronic system for controlling a direct current (DC) motor is presented in Part 1 of the article. The software for the designed motor is described in Part 2. A system for processing data from an infrared transmitter was built. The project was upgraded in successive stages of development, and it ultimately evolved into a small computer with a motor controller. The designed system automatically adjusts the motor’s rotation and speed. The user is tasked only with conveying operational commands. The entire system is based on a single microcontroller. The designed optoelectronic system receives user commands (the program can be modified to support free-space optical communication networks conforming to all communication standards). The system activates the motor, counts the number of rotations and adjusts the motor’s position. The designed system operates on the following principle: the user sends commands to the motor via a remote control with an infrared diode. The keys on the remote control have been programmed with different commands. The transmitted data are processed by the system which activates the motor and sets the desired motor speed. The task is completed, and the system is ready to process the next command. If the number of rotations differs from the preset value, the motor’s position is adjusted. If the physical position of the rotor axis is altered, the system corrects the offset to the last programmed position. The designed system can be easily adapted to various types of motors and IR controllers.